Cyclometalated iridium(iii) complexes with imidazo[4, 5-f][1, 10]phenanthroline derivatives for mitochondrial imaging in living cells. Issue 16 (25th March 2015) - Jin, Chengzhi; Liu, Jiangping; Chen, Yu; Li, Guanying; Guan, Ruilin; Zhang, Pingyu; Ji, Liangnian; Chao, Hui
Abstract : A new series of cyclometalated iridium(iii ) complexes with imidazo[4, 5- f ][1, 10]phenanthroline derivatives, MitoIr1 –MitoIr7, were developed to image mitochondria in living cells. Abstract : A new series of cyclometalated iridium(iii ) complexes with imidazo[4, 5- f ][1, 10]phenanthroline derivatives ( i.e., MitoIr1 –MitoIr7 ) were synthesized and developed to image mitochondria in living cells. In comparison with commercially available mitochondrial trackers, these complexes exhibit a superior capacity to selectively accumulate in mitochondria with no requirement of any membrane permeabilization or replacement of the culture medium. In addition, the excellent photostability under continuous laser irradiation as well as the stable physiological pH resistance of these complexes were confirmed by photobleaching experiments and luminescence measurements. Importantly, MitoIr7, which exhibited both excellent luminescence and high ability to locate in mitochondria, was developed to track the mitochondrial morphological changes over a long period of time.